Կենցաղային տեխնիկայի անվտանգության ապահովան խնդիրն ավագ նախադպրոցական տարիքում - Մանուկյան, Գ. Ա. (Մանկավարժ հրատ․)
Հոդվածում քննարկվում են կենցաղային տեխնիկայի ապահովմանը միտված փորձարարական աշխատանքի արդյունքները, հաստատվում է այս ոլորտում առկա թերացումները, նախադպրոցական տարիքի երեխաների անվտանգության ապահովման հնարավորությունները կենցաղային տեխնիկայի հետ ծանոթացման փուլում: Մշակվել են կենցաղային տեխնիկայի հանդեպ անվտանգությունն ապահովող մանկավարժական տեխնոլոգիաներ և նշված են այդ գործընթացը խթանող մանկավարժական պայմանները: В статье рассматриваются результаты экспериментальной работы по обеспечению безопастности использования бытовой техники, подтверждаются недостатки в этой области, возможности безопасности работы дошкольников с бытовой техникой. На этапе ознакомления разработаны педагогические технологии по обеспечению безопасностной работы с бытовой техникой, указаны педагогические условия, способствующие этому процессу. The issue of child safety is one of the global priorities of the 21st century. The upward developments of social lite show the manifestations of the ever-increasing social instability, as various disasters, man-made dangers are a serious threat to humanity in material and physical terms.In addition, terrorism, crime, natural and technical disasters, wars, etc., on their scale affect not only the lives of adults, but also the lives of children, causing material and serious losses. The main purpose of educating sate behavior is not only to keep children away from the possible dangers of house hold appliances, but also to teach them to avoid dangerous situation while using household appliances, in some cases to prevent possible dangers, to make decisions to maintain their own safety. Pre-school education plays an important role in ensuring a secure lifestyle. The culture of a healthy and sate lifestyle is not initially given to the child, as it is the result of education, upbringing and self-development through consistent work. In order to develop sate behavior, we have studied the pedagogical processes that, as a result of conducting special exercises, lead to the realization of the dangers of household appliances. During the trainings we used several technologies aimed at building skills: pedagogical-organizing technology, valeological tales, information-co-educational technology. The above-mentioned technology include educational games, game-performances, performances, educational computer games, cartoons, etc. Experimental work based on the well-chosen choice of pedagogical technologies has been carried out to clarify the effectiveness of pedagogical technologies aimed at developing safe behavior towards house hold appliances.
Keywords: Մանկավարժություն